Development of Life-Long Learning Skills for grade 10 students by Mobile – Learning (m – Learning) - Wilachai, Anecha; Dokmai, Panwilai; Worakham, Paisarn (Community and Social Development Journal, 2020)
Life-long learning helps people both in knowledge and ability. These encourages people in continuing of learning, always developing themselves, self-care, and be able to choose what to study in accordance with lifestyle and their own work. The learning which could be anywhere and anytime resulting to personal development practical abilities no matter what career they are in. The researcher therefore developed life-long learning skills. The target group was 36 students of grade 10 at Kalasin Pittayasan School, Muang District, Kalasin Province in the 1st semester of 2019 academic year. The research tools were mobile-Learning (m-Learning) activities plans and the life-long learning skills were measured with the 5-levels estimation scale in 5 parts: technology skills, learning skills, searching and analyzing skills, self-reliance skills, and language skills, totally 15 items. The IOC was range 0.8 - 1.0 with the discrimination between .298 - .772, and the reliability between .721 - .865. The action research was operated divided into 2 circles. The statistics for data analysis were mean and standard deviation. At the beginning the targets were 6 students with life - long learning skills at low level (mean = 2.30, Standard Diviation = 0.86) and 3 students with life - long learning skills at lowest level (mean = 1.38, Standard Diviation = 0.66). After the 1st circle of operation was left 4 students with life-long learning skills at low level (mean = 1.93, Standard Diviation = 0.59) and at the end of the 2nd circle, all students hold life-long learning skills at a high level (mean = 4.33, Standard Diviation = 0.67).